Magnesium Sulfate for Neuroprotection. Issue 6 (November 2015) - Unknown
Abstract : Magnesium sulfate administered intravenously to women at risk for early preterm birth can decrease risk of cerebral palsy in their babies. The regime from one of the larger randomized trials that studied magnesium sulfate for neuroprotection should be used. A standard protocol for all women who are appropriate candidates is not yet available because each of the randomized trials used different dosing regimens.